1988
DOI: 10.1007/bf02470855
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic goiters of the mediastinum: Presentation of two cases and review of the literature

Abstract: Two cases of ectopic goiters located in the anterior mediastinum are presented. These comprise 5.1 per cent of our cases of intrathoracic goiters and 1.3 per cent of mediastinal tumors. These benign tumors have been rarely reported in the literatures, however, excision by thoracotomy is the surgical procedure advocated for these cases and the diagnosis is generally established operatively. Angiography and tomography have proved useful in diagnosing and localising these lesions prior to the surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Patients asymptomatic were usually found incidentally via imaging [ 14 ]. Compressive symptoms by the mass may occur [ 3 , 15 ]. Cytologic results demonstrated an ETT, and, if not, our differential diagnosis would be to rule out thymoma and malignant lymphoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients asymptomatic were usually found incidentally via imaging [ 14 ]. Compressive symptoms by the mass may occur [ 3 , 15 ]. Cytologic results demonstrated an ETT, and, if not, our differential diagnosis would be to rule out thymoma and malignant lymphoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complaints related to mediastinal ectopic thyroids are often asymptomatic, and those masses were often incidentally found via imaging modalities [ 9 ]. Symptoms associated with compression of surrounding tissue by the mass may occur, and cases with dyspnea and cough have been reported in the literature [ 3 , 19 ]. In the present case, the mass slightly compressed the trachea, and the patient suffered from a chronic cough; however, it gradually improved and disappeared at the time of surgery, and was therefore judged to be different from the symptom associated with the mass.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the ectopic thyroid in the mediastinum was not connected with the orthotopic thyroid gland, and the blood flow was supplied from the thorax sides, which was demonstrated both on the CT image and in intraoperative findings. It has been reported that sternotomy or thoracotomy is essential for the removal of a mediastinal ectopic goiter, which receives blood flow from the thorax; therefore, in most of the cases, surgical resection was performed through sternotomy or thoracotomy [ 3 , 4 , 6 , 12 , 14 - 17 , 19 ]. However, there have been some reports of mediastinum ectopic thyroids resected only through a cervical incision, but in all cases, concomitant resection of the orthotopic thyroids was performed [ 7 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic growth of germinal nuclei in the thyroglossal duct fixing to a cardiopericardiac mass is presumed to be one of the reasons for occurrence of these rests 3. In a study conducted by Sackett et al ,2 TTR was classified into four grades based on the anatomical relationship with the lower pole of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%